Uncertainty quantification for complex systems : application to the study of cities - Steentoft, Aike Alexander (Nanyang Technological University, 2021)
Human interactions are the fundamental drivers that establish cities as the hubs for innovation and economic growth. Traditional urban planning methods -- aimed to facilitate these interactions -- are however becoming questionable as they are typically based on 'best practice', thus unable to cope with the increasing complexity of today's rapidly evolving cities. The quantitative description of interactivity and its relation to the spatial organization of urban spaces and transportation infrastructure is therefore of fundamental importance.